ASSESSMENT OF THE CURRENT STATE OF INTERNATIONAL BUSINESS TOURISM: A COMPARATIVE ANALYSIS OF GLOBAL AND UKRAINIAN TRENDS - Zghurska, Yu. (Municipal economy of cities. Series: «Economy science», 2023)
The article aims to assess the current development state of international business tourism. It analyses the main trends, problems, and prospects of this industry. The author reviews recent data on the foreign business travel volume, leading countries in this area, and significant market segments. The study highlights the role of modern information technologies and sustainable development in the context of business tourism.